YaHS: yet another Hi-C scaffolding tool - Zhou, Chenxi; McCarthy, Shane A; Durbin, Richard (Bioinformatics (Oxford, England), 2023)
Abstract Summary We present YaHS, a user-friendly command-line tool for the construction of chromosome-scale scaffolds from Hi-C data. It can be run with a single-line command, requires minimal input from users (an assembly file and an alignment file) which is compatible with similar tools and provides assembly results in multiple formats, thereby enabling rapid, robust and scalable construction of high-quality genome assemblies with high accuracy and contiguity. Availability and implementation YaHS is implemented in C and licensed under the MIT License. The source code, documentation and tutorial are available at https://github.com/sanger-tol/yahs. Supplementary information Supplementary data are available at Bioinformatics online.